If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 1 + 3x + 6 = 0 Reorder the terms: 1 + 6 + 3x + 3x = 0 Combine like terms: 1 + 6 = 7 7 + 3x + 3x = 0 Combine like terms: 3x + 3x = 6x 7 + 6x = 0 Solving 7 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 6x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 6x = 0 + -7 6x = 0 + -7 Combine like terms: 0 + -7 = -7 6x = -7 Divide each side by '6'. x = -1.166666667 Simplifying x = -1.166666667
| 8n+(5n+13)=7 | | 9x^3-105x^2-56x=0 | | 3x^3+170x^2-57x=0 | | Y=(4x+3) | | 5a-20/5 | | z^3-3*z^2-3*z^2*i+6*z*i-10*i+2=0 | | z^3-3z^2-3z^2i+6zi-10i+2=0 | | 3x+17-6=21 | | 3(x-a)+b=4x+9 | | 3x-3a+b=4x+9 | | 14v+56-2v=12v+8-13 | | 9v+33=9v+3-9 | | 9+7y=6y | | z^3-6Z^2+6zi-10i+2=0 | | 16x-9=15x+9 | | 16x-9=5x+9 | | 16x-9=15x-9 | | .16y+.03(y+4000)=1830 | | cos(x)+cos(7x)+cos(3x)+cos(5x)=0 | | (x+1)(x+2)-8=0 | | y=2*2-4 | | (3x^2+2xy+2x)dx+(x^2+2y)dy=0 | | x/3-7=20 | | 4(2x+3)-5(4x-6)= | | 3(4+2k)=-2(7+k) | | 12(2h-7)=24(5+3h) | | 5m+4=10(3-9m) | | 60+x+3+4x+8=180 | | 60+x+3+4x+18=180 | | 2x+20+x+20+40=180 | | x+20+120+x=180 | | 40+2x+30+x+20=180 |